Problematika Kebudayaan dalam Penerjemahan Bahasa Arab ke Bahasa Indonesia - Khoirul Huda (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
Translation as an activity and translation as a result of activities cannot be separated from the concept of culture. Translation has an important role in the development of culture, translating means comparing culture. The link between language and culture gives rise to the implication that translation is not only understood as a transfer of form and meaning, but also as a cultural diversion. Consequently, translation activities can not only experience language barriers, but also cultural constraints. In this regard the task of the translator is not just to look for lexical and grammatical equivalents, but also to find appropriate ways to express things in the target language.Looking at the background above, the writer will present briefly in his discussion of cultural problems in translating Arabic into Indonesian. The problem formulation of this discussion is: What are the cultural problems faced by translators of Arabic into Indonesian, and How to deal with cultural problems in translating Arabic into Indonesian.